Preparation method of high-performance foamed ceramic of Dexing copper mine tailing / steel slag / coal gangue system
Through the ball grinding and sintering process, the Dexing copper mineral tail mines, steel residue and coal gangsters are transformed into high -performance foam ceramics, solving the problem of low utilization rate of solid waste, and realizing the efficient utilization and environmental protection effects of resources.
Patent Information
- Application Number
- CN202411534458.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-24
AI Technical Summary
The utilization rate of tailings, steel slag and coal gangue in Dexing copper mine is low, resulting in waste of resources and environmental pollution. It is difficult for the existing technology to effectively utilize these solid wastes in resource utilization.
A planetary ball mill is used to grind copper mine tailings, steel slag and coal gangue into particles of more than 200 mesh, and then dry and mix with a small amount of water according to a specific mass ratio to form a batch material. It is then pressed and formed in a metal mold, and finally sintered in a high-temperature muffle furnace to form high-performance foam ceramics.
Realize the maximum utilization of Dexing copper ore tailings, steel residue and coal gangsters, and prepare foam ceramics with high water, high air pore rate, and high compression intensity. Simple, low cost, controllable production.
Smart Images

Figure CN119350060A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the fields of solid waste recycling, building energy saving and new building ceramic materials, and in particular to a method for preparing high-performance foam ceramics of a full solid waste system using Dexing copper mine tailings / steel slag / coal gangue as raw materials. Background Art
[0002] The large amount of accumulated garbage not only occupies land resources, but also spreads dust in the open air, causing air pollution. Therefore, the efficient resource utilization of industrial solid waste can not only reduce the land occupied by industrial solid waste, but also reduce environmental pollution. The social and ecological benefits are very important.
[0004] In the process of steel smelting, steel slag is one of the by-products, accounting for about 15%-20% of the total crude steel output, and it is increasing rapidly with the increase of world steel production. As a solid waste, steel slag piles not only occupy land, but also bring a series of ecological and environmental pollution problems, and also cause a waste of precious resources to a certain extent. With the increase in its total amount, it greatly hinders the sustainable development of the environment. Therefore, the efficient resource utilization of steel slag is urgent.
[0005] Gangue is the main solid waste in the process of coal mining and processing. However, due to its low calorific value and difficulty in utilization, it is usually piled in the open air and dumped around the mining area, which easily causes environmental pollution such as soil and groundwater. At present, the comprehensive treatment technology of gangue ground is mainly concentrated in gangue power generation, road paving, and building materials production, which can no longer meet the requirements of the increasing amount of gangue treatment year by year. The harmless, resource-based, and large-scale disposal and utilization of gangue solid waste is imminent.
[0006] As a new type of building material, foam ceramics have many advantages such as high temperature stability, thermal insulation, high porosity, etc., and are widely used in thermal insulation, filters, catalyst carriers, etc. At present, there are a large number of research reports on the use of industrial solid waste to prepare foam ceramics. Its low cost, high operating temperature, and environmental protection make it have broad application prospects in the construction industry, which will further promote the transformation and application of related technologies and be conducive to the rational solution of environmental and energy conservation issues.
[0007] In the research on the resource utilization of solid wastes such as copper tailings, steel slag or coal gangue, Chinese patent application number CN202311298674.X discloses a method for preparing a high-whiteness ceramic body and firing method using copper tailings. In addition to copper tailings, the raw materials also include kaolin, potassium feldspar, calcium-based bentonite, boron mud and magnetite tailings. This method has many types of raw materials, a complex heat treatment system, a complexing iron removal agent is added during the preparation process, and the utilization rate of copper tailings is not high. It does not involve the preparation of materials using all solid waste as raw materials, nor does it involve the resource utilization of steel slag and coal gangue.
[0008] Chinese patent application number CN202410272599.8 discloses a method for preparing a ceramic composite material using steel slag, titanium dioxide, graphite powder, starch and adhesive. The preparation process of this method is relatively complicated, and adhesive is added during the preparation process. It does not involve a full solid waste system foam ceramic and its preparation method.
[0009] Chinese patent application number CN202410374491.X discloses a method for preparing a sound-absorbing and sound-insulating ceramic material. The method uses tailings, gelling materials, foaming agents, pore-forming agents, and foam stabilizers as raw materials, wherein the tailings include iron tailings, tungsten tailings, and feldspar tailings. Various raw materials are weighed in proportion, and after wet ball milling, molding, drying, and sintering treatment, a sound-absorbing and sound-insulating ceramic material is obtained. The sound-absorbing and sound-insulating ceramic material prepared by this method requires the addition of pore-forming agents, foam stabilizers, and foaming agents. The production cost is relatively high, and does not involve all-solid waste system foam ceramics and their preparation methods. Summary of the invention
[0010] In order to maximize the utilization of industrial solid waste and effectively solve the problems of low utilization rate and heavy pollution of Dexing copper mine tailings / steel slag / coal gangue, the present invention provides a method of using Dexing copper mine tailings / steel slag / coal gangue as raw materials, making full use of the synergistic-complementary-antagonistic effect between the chemical compositions of the three raw materials to prepare a high-performance foam ceramic material of the full solid waste system, which can be used as building walls and thermal insulation and fireproofing materials.
[0011] The object of the present invention is achieved in this way. A method for preparing high-performance foam ceramics from a full solid waste system, characterized in that the steps are as follows:
[0012] 1) After the Dexing copper mine tailings / steel slag / coal gangue are ball milled by a planetary ball mill, the particle sizes of the three raw materials are all above 200 mesh;
[0013] 2) After the three ball-milled raw materials are completely dried, they are mixed evenly with 3-5% of the total mass of water in a ceramic mortar according to the pre-designed raw material mass ratio to obtain a batch material. The mass percentage of each component is: Dexing copper mine tailings 64-69%, steel slag 7-8%, coal gangue 23-29%;
[0014] 3) The batch material is loaded into a metal mold and pressed at a pressure of 20 MPa using a small manual press to obtain a foam ceramic body;
[0015] 4) placing the foam ceramic body into a high-temperature muffle furnace, heating it to 1200-1260° C. at a heating rate of 5° C. / min, and keeping the temperature for 1 hour, and cooling it along with the furnace to obtain the foam ceramic.
[0016] Preferably, the addition of a small amount of water in the solution plays a role in wetting and bonding properties, is beneficial to the pressing and molding of the raw materials, and gives the ceramic body initial mechanical strength.
[0017] Preferably, the compression molding adopts a single-sided pressurization method.
[0018] The present invention uses the potential synergistic, complementary and antagonistic effects based on the physical and chemical properties of Dexing copper mine tailings / steel slag / coal gangue, scientifically combines and matches the three industrial solid wastes, and realizes the maximum combination of the three solid wastes on the basis of synthesizing high-performance foam ceramics. SiO2 and Al2O3 in the raw material composition can construct the skeleton structure of the foam ceramic during the sintering process, so that the foam ceramic has good mechanical properties and chemical stability. A certain amount of alkali / alkaline earth metal oxides in the chemical composition can be used as sintering aids. Other chemical components (such as Fe2O3) can be used as foaming components to provide conditions for foam ceramics to form a porous structure. In addition to being used as sintering aids, alkali / alkaline earth metal oxides can also react with SiO2 and Al2O3 to generate silicates, aluminates and aluminosilicates, and then form a glass phase. The formed glass phase constitutes the pore wall, wraps the bubbles generated by the foaming composition, and thus forms a porous structure of the foam ceramic. The present invention makes maximum use of Dexing copper mine tailings / steel slag / coal gangue, and has a simple preparation process, low cost and high production controllability. It has the characteristics of high water permeability, high porosity, high compression strength, and will not cause secondary pollution. It can be used as building walls and heat insulation and fireproof materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a physical picture of the foam ceramic prepared in Example 4 of the present invention. DETAILED DESCRIPTION
[0020] The present invention is further described below with reference to the embodiments, but the protection scope of the present invention should not be limited thereto.
[0021] A method for preparing high-performance foam ceramics from a full solid waste system, the steps of which are as follows:
[0022] 1) After the Dexing copper mine tailings / steel slag / coal gangue are ball milled by a planetary ball mill, the particle sizes of the three raw materials are all above 200 mesh;
[0023] 2) After the three ball-milled raw materials are completely dried, they are evenly mixed with 3-5% of the total mass of water in a ceramic mortar according to the pre-designed raw material mass ratio to obtain a batch material. The mass percentage of each component is: 64-69% of Dexing copper mine tailings, 7-8% of steel slag, and 23-29% of coal gangue. The addition of a small amount of water plays a role in wetting and bonding properties, which is beneficial to the pressing and molding of the raw materials, giving the ceramic body initial mechanical strength. The water is decomposed during the later high-temperature sintering process, ensuring that the raw materials of the foam products are all from industrial solid waste;
[0024] 3) The batch material is loaded into a metal mold, and is pressed and molded by a small manual press machine at a pressure of 20 MPa to obtain a foam ceramic body; the pressing and molding is performed by a single-sided press method.
[0025] 4) placing the foam ceramic body into a high-temperature muffle furnace, heating it to 1200-1260° C. at a heating rate of 5° C. / min, and keeping the temperature for 1 hour, and cooling it along with the furnace to obtain the foam ceramic.
[0026] Embodiment 1:
[0027] The Dexing copper mine tailings / steel slag / coal gangue are ball-milled in a planetary ball mill and dried completely. The Dexing copper mine tailings / steel slag / coal gangue are weighed according to the mass percentage of 69 / 8 / 23%, and 3-5% of water of the total mass of the raw materials is added and mixed evenly in a ceramic mortar. Then it is placed in a metal mold and a pressure of 20MPa is applied to press it into a foam ceramic body. The foam ceramic body is then placed in a high-temperature muffle furnace and heated to 1200°C at a uniform rate of 5°C / min and kept warm for 1 hour. After cooling in the furnace, a foam ceramic product is obtained, and its volume density is 0.90g / cm 3 , the porosity is 31.59% and the compression strength is 10.82Mpa.
[0028] Embodiment 2:
[0029] The Dexing copper mine tailings / steel slag / coal gangue are ball-milled in a planetary ball mill and dried completely. The Dexing copper mine tailings / steel slag / coal gangue are weighed according to the mass percentage of 69 / 8 / 23%, and 3-5% of water of the total mass of the raw materials is added and mixed evenly in a ceramic mortar. Then it is placed in a metal mold and pressed into a foam ceramic body under a pressure of 20MPa. The foam ceramic body is then placed in a high-temperature muffle furnace and heated to 1220°C at a uniform rate of 5°C / min and kept warm for 1 hour. After cooling in the furnace, a foam ceramic product is obtained, and its volume density is 0.26g / cm 3 , the porosity is 90.14% and the compressive strength is 0.73MPa.
[0030] Embodiment 3:
[0031] The Dexing copper mine tailings / steel slag / coal gangue are ball-milled in a planetary ball mill and dried completely. The Dexing copper mine tailings / steel slag / coal gangue are weighed according to the mass percentage of 69 / 8 / 23%, and 3-5% of water of the total mass of the raw materials is added and mixed evenly in a ceramic mortar. Then it is placed in a metal mold and pressed into a foam ceramic body under a pressure of 20MPa. The foam ceramic body is then placed in a high-temperature muffle furnace and heated to 1240°C at a uniform rate of 5°C / min and kept warm for 1 hour. After cooling in the furnace, a foam ceramic product is obtained, and its volume density is 0.23g / cm 3 , the porosity is 85.62% and the compressive strength is 0.52MPa.
[0032] Embodiment 4:
[0033] The Dexing copper mine tailings / steel slag / coal gangue are ball-milled in a planetary ball mill and dried completely. The Dexing copper mine tailings / steel slag / coal gangue are weighed according to the mass percentage of 64 / 7 / 29%, and 3-5% of water of the total mass of the raw materials are added and mixed evenly in a ceramic mortar. Then put it into a metal mold and apply a pressure of 20MPa to press it into a foam ceramic body. Then place the foam ceramic body in a high-temperature muffle furnace and heat it to 1200℃ at a uniform rate of 5℃ / min, and keep it warm for 1 hour. After cooling with the furnace, a foam ceramic product is obtained, and its volume density is 0.35g / cm 3 , porosity is 72.43%, and compressive strength is 3.22MPa. (See Figure 1 )
[0034] Embodiment 5:
[0035] The Dexing copper mine tailings / steel slag / coal gangue are ball-milled in a planetary ball mill and dried completely. The Dexing copper mine tailings / steel slag / coal gangue are weighed according to the mass percentage of 64 / 7 / 29%, and 3-5% of water of the total mass of the raw materials are added and mixed evenly in a ceramic mortar. Then put it into a metal mold and apply a pressure of 20MPa to press it into a foam ceramic body. Then place the foam ceramic body in a high-temperature muffle furnace and heat it to 1220℃ at a uniform rate of 5℃ / min, and keep it warm for 1 hour. After cooling in the furnace, a foam ceramic product is obtained, and its volume density is 0.28g / cm 3 , the porosity is 89.60% and the compressive strength is 1.40MPa.
[0036] Embodiment 6:
[0037] The Dexing copper mine tailings / steel slag / coal gangue are ball-milled in a planetary ball mill and dried completely. The Dexing copper mine tailings / steel slag / coal gangue are weighed according to the mass percentage of 64 / 7 / 29%, and 3-5% of water of the total mass of the raw materials are added and mixed evenly in a ceramic mortar. Then put it into a metal mold and apply a pressure of 20MPa to press it into a foam ceramic body. Then place the foam ceramic body in a high-temperature muffle furnace and heat it to 1240℃ at a uniform rate of 5℃ / min, and keep it warm for 1 hour. After cooling in the furnace, a foam ceramic product is obtained, and its volume density is 0.33g / cm 3 , the porosity is 83.91% and the compressive strength is 0.77MPa.
[0038] Embodiment 7:
[0039] The Dexing copper mine tailings / steel slag / coal gangue are ball-milled in a planetary ball mill and dried completely. The Dexing copper mine tailings / steel slag / coal gangue are weighed according to the mass percentage of 64 / 7 / 29%, and 3-5% of water of the total mass of the raw materials are added and mixed evenly in a ceramic mortar. Then put it into a metal mold and apply a pressure of 20MPa to press it into a foam ceramic body. Then place the foam ceramic body in a high-temperature muffle furnace and heat it to 1260℃ at a uniform rate of 5℃ / min, and keep it warm for 1 hour. After cooling in the furnace, a foam ceramic product is obtained, and its volume density is 0.43g / cm 3 , the porosity is 63.90% and the compressive strength is 1.26MPa.
[0040] The block density in all examples is measured according to GB / T 3810.3-2006 “Test methods for ceramic tiles Part 3 Determination of water absorption, apparent porosity, apparent relative density and bulk density”.
[0041] The porosity in all examples is measured according to GB / T 5071-2013 “Test method for true density of refractory materials”.
[0042] The flexural strength of the samples in all the examples was measured according to GB / T 1965-1996 “Test method for flexural strength of porous ceramics”.
[0043] Table 1 Performance parameters of foam ceramics prepared in Examples 1-7
[0044]
[0045] In the foam ceramics prepared by the present invention, Dexing copper mine tailings / steel slag / coal gangue account for 100% of the total mass of raw materials. Among them, SiO2 and Al2O3 in the raw material components can construct the skeleton structure of the foam ceramics during the sintering process, giving it good mechanical properties and chemical stability. A certain amount of alkali / alkaline earth metal oxides in the chemical composition can be used as sintering aids to reduce the sintering temperature. Other chemical components (such as Fe2O3) can be used as foaming components to provide conditions for the foam ceramics to form a porous structure. In addition to being a sintering aid, alkali / alkaline earth metal oxides can also react with SiO2 and Al2O3 to generate silicates, aluminates and aluminosilicates, and then form a glass phase. The formed glass phase constitutes the pore wall, wraps the bubbles generated by the foaming composition, thereby forming a foam ceramic with a porous structure. In addition, in the raw material chemical composition of the foam ceramics, heavy metal ions play multiple roles. First, they can effectively adjust the viscosity of the glass phase, thereby affecting the pore size distribution of the internal pore structure of the foam ceramic material. By optimizing the pore size distribution, the comprehensive performance of foam ceramics can be significantly improved, including key indicators such as mechanical strength, thermal stability, and sound insulation effect. Secondly, the glass phase formed by heavy metal ions during the preparation process is fixed by chemical bonding or physical embedding, or enters the newly formed crystal phase by ion substitution. This solidification mechanism ensures the stability and safety of heavy metal ions in foam ceramics, greatly reduces the risk of leakage and release during production and use, and prevents the prepared foam ceramics from secondary pollution. Among the raw materials provided by the present invention, the three raw materials are processed into fine particles by a ball mill, and the particle size obtained by sieving is above 200 mesh. After all the raw materials after ball milling are completely dried, they are evenly mixed with 3-5% of the total mass of the raw materials in a ceramic mortar according to a pre-designed mass ratio to obtain a batch material. The batch material is loaded into a mold, pressed into shape by a small manual sample press, and then sintered at high temperature and kept warm for a certain period of time, and cooled with the furnace to obtain a foam ceramic.
[0046] The method for preparing high-performance foam ceramics from a full solid waste system of the present invention also includes the following preferred embodiments:
[0047] In a preferred solution, the foam ceramic body is placed in a high-temperature muffle furnace, heated to 1200-1260° C. at a heating rate of 5° C. / min, and kept warm for 1 hour.
[0048] In the preferred solution, the addition of water can make the raw material particles have a certain bonding force, which is conducive to compression molding, and the water is decomposed in the later high-temperature sintering process, ensuring that the raw materials of the foam ceramic products are all from industrial solid waste.
[0049] 1) In the chemical composition of the raw materials, SiO2 / Al2O3 can construct the skeleton structure of foam ceramics during the sintering process, giving the foam ceramics good mechanical properties, thermal properties and chemical stability.
[0050] 2) In the chemical composition of raw materials, alkali / alkaline earth / transition metal oxides as sintering aids can reduce the sintering temperature on the one hand; on the other hand, they can react with SiO2 and Al2O3 to form silicates, aluminates, and aluminosilicates, and then form a glass phase. The formed glass phase constitutes the pore wall, wraps the bubbles generated by the foaming composition, and thus forms a porous structure of foamed ceramics.
[0051] In summary, the technical advantages of the present invention bring particularly excellent technical effects:
[0052] 1) The synergistic, complementary and antagonistic effects between the chemical compositions of Dexing copper mine tailings / steel slag / coal gangue were fully utilized to successfully prepare a full solid waste system foam ceramic product with excellent comprehensive performance. The solid waste introduction rate of the obtained foam ceramic reached 100%, realizing the maximum utilization of Dexing copper mine tailings / steel slag / coal gangue.
[0053] 2) The prepared foam ceramic has a simple preparation process, low cost and high production controllability.
[0054] 3) The prepared foam ceramics have the characteristics of low bulk density, high porosity, high compressive strength, and no secondary pollution; specifically, the bulk density of the foam ceramics is 0.23-0.90g / cm 3 The porosity is 31.59-90.14%, and the compression strength is 0.52-10.82MPa. It can be used in the fields of building walls and thermal insulation and fireproof materials.
Claims
1. A method for preparing high-performance ring foam ceramics from a full solid waste system, characterized in that: The steps are as follows: 1) The particle size range of the selected raw materials is as follows: the particle size of Dexing copper mine tailings, steel slag and coal gangue are all above 200 mesh; 2) After the three ball-milled raw materials are completely dried, they are mixed in a ceramic mortar according to the pre-designed raw material mass ratio, and then 3-5% of the total weight of the raw materials are added and mixed evenly to obtain a batch material. The mass percentage of each component is: Dexing copper mine tailings 64-69%, steel slag 7-8%, coal gangue 23-29%; 3) The batch material is loaded into a metal mold and pressed at a pressure of 20 MPa using a small manual press to obtain a foam ceramic body; 4) placing the foam ceramic body into a high-temperature muffle furnace, heating it to 1200-1260° C. at a heating rate of 5° C. / min, and keeping the temperature for 1 hour, and cooling it along with the furnace to obtain the foam ceramic.
2. The method for preparing a high-performance foam ceramic from a full solid waste system according to claim 1, characterized in that: No binder is added and the utilization rate of industrial solid waste is 100%.
3. The method for preparing a high-performance foam ceramic from a full solid waste system according to claim 1, characterized in that: The compression molding adopts a single-side pressurization method.
Citation Information
Patent Citations
Coal gangue-pulverized fuel ash-silica sand tailing system all-waste-residue foam ceramic and preparation method thereof
CN108395271A